Allelopathic pathways and impacts of Chenopodium species via leachates, decaying residues, and essential oils - Abeer Al-Andal; Asmaa M. Radwan; AbdElRaheim M. Donia; Mohamed A. Balah (PLoS ONE, 2025)
The potentials of Chenopodium species are important for both the environment and agricultural production. To comprehend their effects, their allelopathic pathways were investigated. The impacts of C. album, C. murale, and C. ambrosioides weeds were compared via leachates of water extracts, decaying residues, and volatilization and measured biologically and chemically on plant traits and soil characteristics. The allelopathic effect of water extracts from the aboveground parts was more potent than that from the subterranean parts, significantly influenced by the plant parts and concentrations. The allelochemicals determined by LC-ESI-MS were coumaric and ferulic acid, with concentrations of 4.74 and 5.72 μg ml-1 for C. album, 7.07 and 5.71 μg ml-1 for C. murale, and 8.88 and 4.82 μg ml-1 for C. ambrosioides, respectively. The allelopathic effect of incorporated residues into soil was affected significantly by plant types, concentration, and their interactions. The essential oils of shoot parts showed the strongest suppression in B. rigidus and C. arvensis germination and growth. The principal components of essential oils determined by GC-MS were ascaridole (C. ambrosioides), carvacrol (C. murale), and carvacrol (C. album) with concentrations of 8.87%, 10.64%, and 8.43%, respectively. Notably, C. ambrosioides and C. murale demonstrated the strongest inhibitory effects, followed by C. album suggested to be used as herbicide treatments in the future. Chenopodium species exert significant inhibitory effects by releasing allelochemicals against several tested species. Therefore, allelopathy appears to be responsible for the nearby plant structure through the action of their bioactive metabolites.